Polyethylene Glycol-Modified Poly(Styrene-co-Ethylene/Butylene-co-Styrene)/Carbon Nanotubes Composite for Humidity Sensing - Mičušík, Matej; Chatzimanolis, Christos; Tabačiarová, Jana; Kollár, Jozef; Kyritsis, Apostolos; Pissis, Polycarpos; Pionteck, Jürgen; Vegso, Karol; Siffalovic, Peter; Majkova, Eva; Omastová, Mária (Frontiers in Materials, 2019)
Polymeric composites of the linear triblock copolymer poly(styrene-co-ethylene/butylene-co-styrene) grafted with maleic anhydride units (SEBS-MA) or MA modified by hydrophilic polyethylene glycol (PEG) and containing various amounts of multiwall carbon nanotubes (MWCNTs) as conducting filler—were prepared by solvent casting. The MWCNT surface was modified by a non-covalent approach with a pyrene-based surfactant to achieve a homogeneous dispersion of the conducting filler within the polymeric matrix. The dispersion of the unmodified and surfactant-modified MWCNTs within the elastomeric SEBS-MA and SEBS-MA-PEG matrices was characterized by studying the morphology by TEM and SAXS. Dynamical mechanical analysis was used to evaluate the interaction between the MWCNTs and copolymer matrix. The electrical conductivity of the prepared composites was measured by dielectric relaxation spectroscopy, and the percolation threshold was calculated. The prepared elastomeric composites were characterized and studied as humidity sensor. Our results demonstrated that at MWCNTs concentration slightly above the percolation threshold could result in large signal changes. In our system, good results were obtained for MWCNT loading of 2 wt% and an 0.1 mm thin composite film. The thickness of the tested elastomeric composites and the source current appear to be very important factors that influence the sensing performance.